Pandangan Hukum Islam Terhadap Perkawinan Beda Agama Dalam Perspektif Normatif Yuridis Psikologi - Erwansyah, Tomy; Jayusman, Jayusman; Zaki, Muhammad (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
Interfaith marriage refers to a union between individuals adhering to different religious traditions. In Indonesia, characterized by its religious diversity, individuals generally maintain their commitment to their respective faiths. This research aims to present an in-depth exploration of interfaith marriage within the framework of Islamic law, serving as a valuable reference for legal and social studies. As outlined in Article 40(c) of the Compilation of Islamic Law (KHI), muslim men are strictly forbidden from entering into marriage with women who adhere to a different religion. Similarly, Article 44 of the same legal framework explicitly forbids Muslim women from entering into marriage with non-Muslim men. This research employs a normative legal method, relying on secondary data sources such as legislation, online resources, and scholarly literature. Data collection was conducted through a library research approach, involving the analysis and interpretation of relevant theories and literature. The findings suggest that interfaith marriages are influenced by the plurality of religions in Indonesia and by patterns of social interaction. Nonetheless, in Islamic teachings, Marriage is conceptualized as as a union that encompasses both physical and spiritual bonds between a man and a woman, aimed at forming a harmonious and enduring family founded upon faith in the One Supreme God